Amplification-free detection of plant pathogens by improved CRISPR-Cas12a systems: a case study on phytoplasma - Lagner, Joseph R.; Newberry, Eric A.; Rivera, Yazmín; Zhang, Liyang; Vakulskas, Christopher A.; Qi, Yiping (Frontiers in Plant Science, 2025)
CRISPR-based disease detection has the potential to profoundly change how pathogens are detected in plant materials. However, there has been a lack of research directed into improving explicitly the CRISPR components that define these detection assays. To fill this technology gap, we have designed and optimized our CRISPR-Cas12a based detection platform by showcasing its capability of detecting a plant pathogen group of rising importance, Candidatus Phytoplasma. Most assays utilize isothermal pre-amplification steps, which may boost sensitivity yet often lead to false positives. Aiming for a pre-amplification-free assay to maintain accuracy, we screened multiple Cas12a orthologs and variants and found LbCas12a-Ultra to be the most sensitive Cas12a. We further improved the detection system by using stem-loop reporters of various sizes and found 7nt stem-loop significantly outperformed other stem-loop sizes as well as the commonly used linear reporters. When the 7nt stem-loop reporter was combined with the best-performing LbCas12a-Ultra, we found a 10-fold increase in sensitivity over the standard LbCas12a with the linear reporter detection assay. To enhance the coverage of highly diverse phytoplasmas, we tested a multiplex detection method predicted to target nearly 100% of all documented phytoplasma species on NCBI. A lateral flow assay was also developed to accommodate instrument-free detection with the optimized reagents. Our study demonstrates an improved CRISPR-Cas12a detection system that has wide applications for plant pathogen detection and can be easily integrated into almost any other Cas12a-based detection platform for boosted sensitivity.